Peran Bank Indonesia Kantor Perwakilan Wilayah (KPW) Jambi Dalam Penerapan Keuangan Inklusif Pada UMKM Kota Jambi - Ali Topan; Sissah Sissah; Nurfitri martaliah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
One of the government's efforts to overcome ongoing social protection problems is to encourage the development of micro, small and medium enterprises (MSMEs). The development of MSMEs, especially in Jambi City, has experienced a very large increase, namely 47,813 in 2021 and increased drastically in 2022, namely 50,747. This means that the development of MSMEs in Jambi City has increased by 6.13%. This increase is an effort by the Jambi Provincial Government to encourage the development of MSMEs by synchronizing MSME empowerment programs in each district and city. This research aims to determine the role of Bank Indonesia Jambi Regional Representative Office (Kpw) in implementing inclusive finance in Jambi City MSMEs. This research uses a qualitative approach which is a type of analysis that produces findings that cannot be obtained using statistical methods or other quantitative techniques where Jambi City MSMEs are the object of this research. The research results show that the role of Bank Indonesia KPw Jambi in implementing inclusive finance for Jambi MSMEs is providing information and facilitators in the socialization of inclusive finance, providing knowledge in inclusive financial education and monitoring and evaluating socialization and education activities. Meanwhile, Bank Indonesia KPw Jambi's obstacles in implementing inclusive finance for Jambi MSMEs consist of unequal reach or accessibility and Human Resources (HR) and understanding of the audience.